Linkages between leaf traits and productivity in two resource-limited ecosystems - Chinchilla Soto, Isabel (The University of Edinburgh, 2014)
Leaf traits have long been used to classify and characterise species in natural ecosystems. In addition, leaf traits provide important information about plants’ strategies for the use of resources and can be used to improve our understanding of ecosystem level processes such as nutrient cycling and carbon allocation. To explore the linkages between leaf traits and productivity, we worked in two resource-limited ecosystems (a grassland and a forest), and used leaf traits to understand how species respond to changes in available resources and their relationship to ecosystem processes. We worked in a species rich limestone-grassland located in central England, which has been subjected to long-term climatic manipulation (winter warming, summer drought and extra summer rainfall). We characterised species composition in terms of their identity, abundance and leaf structural properties (nitrogen content and leaf mass per area (LMA)) in the main treatments and the control. We found that change in species abundance was the most important factor to understand the differences in productivity (above ground biomass and total foliar nitrogen). We then measured CO2 exchange at ecosystem level, using a chamber technique, and assessed the treatments’ effect on the gross primary productivity (GPP) and ecosystem respiration (Reco). GPP and Reco were controlled by soil moisture and above ground biomass but also influenced by the conditions experienced during the growing season prior to the measuring period. Our second location was a post-disturbance chronosequence in a seasonally dry tropical forest in Costa Rica and we used leaf level gas exchange measurements to explore the role of nitrogen (N) and phosphorus (P) on the temporal-spatial variation of photosynthesis of dominant species. We found that photosynthetic efficiency was strongly linked to leaf N and P content, but that there was an important seasonal pattern on this relationship likely associated to P remobilization. Additionally we found seasonal changes in resources (water, nutrients) had a larger impact on the photosynthetic parameters than changes along the chronosequence. The two ecosystems studied for this thesis are contrasting in their physiognomy, species composition and climate, but are also characterised by species whose structural traits (high LMA and high C:N ratio) are likely to have a significant impact on the nutrient cycling processes. We learned that leaf traits provide important information about species strategies and their usage of resources and they can also aid to address questions at ecosystem level in time and space, either through simple aggregation or as emergent properties. Additionally, the traits explored are important input information to up-scale processes from leaf to the ecosystem level, a step needed to address the effect changes in resources will have on the seasonally dry tropical forest and grasslands, which represent a significant fraction of the total global carbon storage.
Keywords: Seasonally dry forest; Costa Rica; Calcareous grassland; Carboxylation rate; Gross primary productivity